Response of the soil microbial community to petroleum hydrocarbon stress shows a threshold effect: research on aged realistic contaminated fields - Jia, Wenjuan; Cheng, Lirong; Tan, Qiuyang; Liu, Yueqiao; Dou, Junfeng; Yang, Kai; Yang, Qing; Wang, Senjie; Li, Jing; Niu, Geng; Zheng, Lei; Ding, Aizhong (Frontiers in Microbiology, 2023)
Microbes play key roles in maintaining soil ecological functions. Petroleum hydrocarbon contamination is expected to affect microbial ecological characteristics and the ecological services they provide. In this study, the multifunctionalities of contaminated and uncontaminated soils in an aged petroleum hydrocarbon-contaminated field and their correlation with soil microbial characteristics were analysed to explore the effect of petroleum hydrocarbons on soil microbes. The results indicated that high concentrations of petroleum hydrocarbons (565-2910 mg•kg-1, heavy contamination) reduced soil multifunctionality, while low concentrations of petroleum hydrocarbons (13-275 mg•kg-1, light contamination) might increase soil multifunctionality. In addition, light contamination promoted the growth of denitrifying microbes (Xanthomonadaceae and Comamonadaceae) (p<0.05), increasing the Shannon index of the community (p<0.01) and enhancing the microbial interactions, while heavy contamination stimulated the growth of hydrocarbon-degrading microbes (Pseudomonadaceae and Hydrogenophilaceae) (p<0.01, p<0.05), reducing the Chao index of the community (p<0.05), simplifying the microbial co-occurrence network, and increasing the niche overlap of keystone families. Our study demonstrated that light petroleum hydrocarbon contamination has a certain improvement effect on soil multifunctionalities and microbial characteristics. Only when the contaminant concentration reaches a certain threshold can it show an inhibitory effect, which has significance for the protection and management of petroleum hydrocarbon-contaminated soil.